Endogenous antisense RNA curbs CD39 expression in Crohn’s disease - Rasika P. Harshe (Nature Portfolio, 2020)
CD39 is an ectonucleotidase associated with immunoregulatory function. Here authors show regulation of CD39 expression by an endogenous antisense RNA moiety transcribed from the 3‘ end of CD39/ENTPD1 which when itself is silenced results in amelioration of pathology in an animal model of colitis.